ASSESSING CONGREGANTS PERCEPTION OF VULNERABILITY OF CHURCH BUILDINGS TO SECURITY THREATS IN NAIROBI COUNTY, KENYA - Baraza, Hudson (Advances in Social Sciences Research Journal, 2021)
This paper uses data collected for an MA Thesis on Assessing Congregants’ perception of Vulnerability of Church Buildings to security threats in Nairobi County, Kenya. The study has been necessitated by increased cases of targeted criminal attacks on congregants and church buildings in addition to increased perceptions of congregants as soft targets of insecurity, more pertinently in Nairobi County. The study will be guided by the following objectives; to investigate the nature of perceived vulnerability against church buildings; to explore congregant’s perceptions of what constitutes church buildings security and safety; to establish congregant’s perceptions of their level of preparedness in case of a criminal attack while in church buildings service; and to determine the congregant’s perceptions of what they think should be done to secure church buildings in Nairobi County Kenya. This study was grounded by two theories; Defensive Space Concept and Crime Prevention through Environmental Design (CPTED). This study adopted a cross-sectional survey design while Stratified random sampling technique was used to pick all the main respondents. Questionnaires were used to collect data from 182 members of each church (main respondents). In addition, Key Informants (K.I) guide was used to collect qualitative data from 8 K.I who include 4 Priests (1 from each church), and 4 security guards (one from each church). Data was analyzed with the aid of Statistical Package for Social Sciences (SPSS) and results presented using tables, bar and pie charts. The study results revealed that violent attacks against the churches in Nairobi county are on the increase (72%) and that the violent attacks against the churches in Nairobi county have inspired fear among church attendants (68.1%). Further, results showed the gun attacks were the most prevalent in church buildings (29.7%) closely followed by knife attacks (29.1%), explosive attacks (20.3%), suicide bombs (13.2%). Further, the results have revealed that some churches had employed various measures to counter violent attacks that included amongst other measures employed full time trained security staff to manage such incidents. Congregant’s perceptions on violent attacks against churches include; Knife and explosive attacks during services, but which have prompted fears of future gun or other terror attacks as is the case in other countries. According to the study; main measure of church security and safety included the Perimeter Walls, use of Surveillance cameras, use of Metal Detectors in church entrances, and heavy barriers in church entrance amongst other measures. As a policy measure, the study recommended formulation of standard security and safety measures applicable to all places of worship in Kenya that include; permanent security staff and armed security in all places of worship.